2015
DOI: 10.1212/wnl.0000000000001721
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic neurologic disorders in small cell lung carcinoma

Abstract: Objective: To determine the frequency and range of paraneoplastic neurologic disorders (PNDs) and neuronal antibodies in small cell lung carcinoma (SCLC).Methods: Two hundred sixty-four consecutive patients with biopsy-proven SCLC were recruited at the time of tumor diagnosis. All patients underwent full neurologic examination. Serum samples were taken prior to chemotherapy and analyzed for 15 neuronal antibodies. Thirty-eight healthy controls were analyzed in parallel.Results: PNDs were quite prevalent (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 23 publications
(24 reference statements)
7
84
3
1
Order By: Relevance
“…The results of our study confirm that neural autoantibodies are frequently found in patients with SCLC, even in neurologically asymptomatic patients, as we previously reported for patients with thymoma . Interestingly, IgGs targeting extracellular domains of plasma membrane antigens (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study confirm that neural autoantibodies are frequently found in patients with SCLC, even in neurologically asymptomatic patients, as we previously reported for patients with thymoma . Interestingly, IgGs targeting extracellular domains of plasma membrane antigens (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The profile of neural autoantibodies in a patient's serum reflects the onconeural antigens expressed by the tumor . It is not unusual for multiple autoantibodies and paraneoplastic disorders to co‐exist in one patient …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of preexisting neural antigen‐specific cells in those with or without disease may be consistent with the frequent detection of neurological autoantibodies, particularly of the IgM subclass, in healthy control subjects 18. Similarly, screening of patients without neurological symptoms who have tumors and paraneoplastic autoantibodies, for example, GABA B ‐receptor antibodies and small cell lung carcinoma,19 may identify those with a potentially increased rate of irAEs. As an alternative to a T cell‐directed mechanism of action, as PD‐1 and CTLA‐4 are also expressed on B cells and some myeloid cells, and PD‐L1 on neurons and tumor cells, the checkpoint inhibitors may have additional direct actions via other cell types 2.…”
Section: Discussionsupporting
confidence: 52%
“…36 One or more SCLC-related autoantibodies are demonstrable in the serum of 90% of patients with SCLC who present with neurologic impairment unrelated to metastases and in 40% of SCLC patients without any evident neurologic disorder. 37 Multiple neural-specific IgGs and paraneoplastic disorders often coexist in a single patient. 37 The SCLC-related IgGs identified most commonly are specific for SOX transcription factor proteins (SOX1 and SOX2), Hu proteins (antineuronal nuclear autoantibody [ANNA] type 1), voltage-gated calcium channels (VGCCs; P/Q type and N type), collapsin response-mediator protein 5 (CRMP5), metabotropic g-aminobutyric acid (GABA) type B receptors, amphiphysin, and microtubule-associated protein 1B (antigen of Purkinje cell cytoplasmic autoantibody [PCA] type 2).…”
Section: Small Cell Lung Cancermentioning
confidence: 99%